Healthy Life-Based Analytical Reading Material for Nursing Assistants Program in Vocational School: Students’ Needs Analysis - Desi Ramasari; Rita Inderawati; Soni Mirizon (STAI Hubbulwathan Duri, 2023)
This study aimed to assess the needs of the healthy life habit Nursing Assistant study program at a vocational high school for developing English reading materials. This study is part of the RD (Research and Development), and the data were gathered and evaluated using a questionnaire and semi-structured interviews—the technique for selecting the sample using purposive sampling. The sample of this study was 39 students, four teachers, and two stakeholders (curriculum assistant and the head of the nursing assistant study program) at Vocational High School in Betung. Both quantitative and qualitative methods are used to examine the data. Quantitative methods evaluate questionnaire data, whereas qualitative methods analyze and interpret interview data. The result of this study: 1) Students had basic English. 2) English was essential for the student's career. 3) Multiple-choice and essay questions are the most common test. 4) English reading was necessary for the subject matter. 5) Students must understand the knowledge of healthy lifestyles. 6) There were no English health life materials. 7) Healthy living habits in reading are meant to improve student's study skills and comprehension of healthy life habits. 8) English reading content must include healthy life's physical, nutritional, mental, environmental, emotional, social, and intellectual aspects. The study concluded that designing extra analytical exposition reading materials with healthy living practices that meet the student's English level and boosts the student study program.